Industrial Network Membership: reducing psychic distance hazards in internationalization of firms - Santos, João Carvalho; Ferreira, Manuel Portugal; Reis, Nuno Manuel Rosa dos (Review of Business Management, 2012)
The network approach to internationalization of firms has been the research focus of many international business scholars. Firms are increasingly involved in international business ventures and arguably need to learn to adapt to the idiosyncratic milieus of foreign markets. This paper proposes a conceptual model suggesting that integration in industrial networks strengthens corporate competitiveness in international markets. Network membership provides access to knowledge and a wider array of physical, technical, reputational and financial resources that facilitate adaptation to the various dimensions – economic, political, legal, cultural – of international business environments. Membership in social and business networks is likely to ease internationalization by reducing the psychic distance perceived by firms. Key words: Networks. Internationalization theories. Psychic distance.